Prescribing trends in bipolar disorder: cohort study in the United Kingdom THIN primary care database 1995-2009. - Joseph Hayes; Philip Prah; Irwin Nazareth; Michael King; Kate Walters; Irene Petersen; David Osborn (PLoS ONE)
Objectives To determine changes in prescribing patterns in primary care of antipsychotic and mood stabiliser medication in a representative sample of patients with bipolar disorder in the United Kingdom over a fifteen year period and association with socio-demographic factors. Methods We identified 4700 patients in the Health Improvement Network (THIN) primary care database, who had received treatment for bipolar disorder between 1995 and 2009. The proportion of time for which each individual was prescribed a particular medication was studied, along with variation by sex, age and social depravation status (quintiles of Townsend scores). The number of drugs an individual was taking within a particular year was also examined. Results In 1995, 40.6% of patients with bipolar disorder were prescribed a psychotropic medication at least twice. By 2009 this had increased to 78.5% of patients. Valproate registered with the greatest increase in use (22.7%) followed by olanzapine (15.7%) and quetiapine (9.9%). There were differences by age and sex; with young (18-30 year old) women having the biggest increase in proportion of time on medication. There were no differences by social deprivation status. By 2009, 34.2% of women of childbearing age were treated with valproate. Conclusions Lithium use overall remained relatively constant, whilst second generation antipsychotic and valproate use increased dramatically. Changes in prescribing practice preceded published trial evidence, especially with the use of second generation antipsychotics, perhaps with inferences being made from treatment of schizophrenia and use of first generation antipsychotics. Women of childbearing age were prescribed valproate frequently, against best advice.